Allogeneic Hematopoietic Cell Transplant for Prolymphocytic Leukemia - Kalaycio, Matt E. (2009)
The poor prognosis of patients with prolymphocytic leukemia (PLL) has led some clinicians to recommend allogeneic hematopoietic cell transplant (HCT). However, the data to support this approach is limited to case-reports and small case-series. We reviewed the database of the Center for International Blood & Marrow Transplant Research to determine outcomes after allotransplant for patients with PLL. We identified 47 patients with a median age of 54 years (range, 30–75). With a median follow-up of 13 months, progression-free survival was 33% (95% Confidence Interval 20–47%) at 2 years. The most common cause of death was relapse or progression in 49%. The cumulative incidence of treatment-related mortality at 1-year post transplant was 28%. The small patient population prohibited prognostic factor analysis but these data support consideration of allotransplant for PLL. Further study of a larger population of patients is needed to determine which patients are more likely to benefit.